Los “Poemas underwood” de Martín Adán - Vich, Víctor (2017)
In this essay I study the “Underwood Poems” that Martin Adan included in “La Casa de Carton” (1928). Its formal characteristics make these poems one of the most important texts of the Peruvian vanguard, as well as they establish one of the most resounding criticism to the modernity discourse of the era. I am particularly interested in analyzing one of the main images of this poem in order to trace not only the principal social changes that are represented but also how the poetic voice configures a compelling armor of critical responses to these changes.